ANALISIS STRATEGI LEMBAGA PENJAMIAN MUTU MELALUI PROGRAM KHUSUS KONSEP LIMA MENARA ILMU DI UNIVERSITAS ISLAM MADURA: ANALISIS STRATEGI LEMBAGA PENJAMIAN MUTU MELALUI PROGRAM KHUSUS KONSEP LIMA MENARA ILMU DI UNIVERSITAS ISLAM MADURA - Kholifatus Zahroh (Akademika: Jurnal Keagamaan dan Pendidikan, 2024)
A quality assurance institution (LPMU) in a tertiary institution has a very vital role in producing quality education in the management of tertiary institutions. SPM Dikti aims to guarantee the fulfillment of Dikti Standards in a systemic and sustainable manner, so that a culture of quality grows and develops. Thus, SPMI as one of the sub-systems of the Higher Education SPM, aims to improve the quality of higher education in a systemic and sustainable manner through the Higher Education Standards PPEPP, in other words, the results of a quality culture will grow and develop. Of course the goal will be achieved if each tertiary institution has implemented SPMI properly and correctly, while its external accreditation meets external needs.